SYMBOL ANALYSIS OF THE WEKASAN REBO TRADITION AND TRUST OF THE JAPANESE VILLAGE COMMUNITY, MEJOBO DISTRICT, KUDUS REGENCY - Lutfi, Khairul; Ilham, Lailul (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2022)
Java is one of the areas that is rich in culture and since hundreds of years ago the Javanese people have carried out the culture of their ancestors so that the Javanese people are very familiar with local culture and including the mysticism of culture itself. This cultural diversity then encourages researchers to conduct in-depth research related to the traditions or culture of the Javanese people, especially the Rebo Wekasan tradition in the Japanese village community. This tradition is still preserved and commemorated by the community every last Wednesday in the month of Safar and in its current development the tradition is commemorated for several days with a series of various religious activities. Specifically, this study examines the symbolic aspects contained in the Rebo Wekasan tradition and how the Japanese Village community believes in the tradition to maintain it to this day.